2014
DOI: 10.4236/gep.2014.21001
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Improved Cookstoves to Reduce Indoor Air Pollution in Developing Countries. The Case of the Cassamance Natural Subregion, Western Africa

Abstract: The Spanish NGO "Alianza por la Solidaridad" has installed improved cookstoves in 3000 households during 2012 and 2013 to improve energy efficiency reducing fuelwood consumption and to improve indoor air quality. The type of cookstoves were Noflaye Jeeg and Noflaye Jaboot and were installed in the Cassamance Natural Subregion covering part of Senegal, The Gambia and Guinea-Bissau. The Technical University of Madrid (UPM) has conducted a field study on a sample of these households to assess the effect of improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 5 publications
(4 reference statements)
1
12
0
Order By: Relevance
“…Inefficient burning of solid fuels for cooking causes indoor air pollution from various types of pollutants. Exposure to these pollutants for long periods of time has several health impacts (WHO, 2006;SOTA et al, 2014), such as the emergence of disease (lung cancer, chronic obstructive pulmonary disease, pneumonia and tuberculosis), and cardiovascular, eye and gestational problems (ROYAL COLLEGE OF PHYSICIANS, 2016).…”
Section: Negative Impacts Of Traditional Stovesmentioning
confidence: 99%
“…Inefficient burning of solid fuels for cooking causes indoor air pollution from various types of pollutants. Exposure to these pollutants for long periods of time has several health impacts (WHO, 2006;SOTA et al, 2014), such as the emergence of disease (lung cancer, chronic obstructive pulmonary disease, pneumonia and tuberculosis), and cardiovascular, eye and gestational problems (ROYAL COLLEGE OF PHYSICIANS, 2016).…”
Section: Negative Impacts Of Traditional Stovesmentioning
confidence: 99%
“…Across a 100-year horizon, Noflaye Jegg showed an overall increase of 88% global warming potential in comparison to the traditional stove. In consequence, while the use of Noflaye Jegg has clear benefits for improving indoor air quality (Sota et al, 2014 and chapter 5 of this thesis), results suggest that this type of rocket stove, under typical cooking practices and fuelwood used Senegal, leads to negative climate effects with regard to carbonaceous aerosol emissions.…”
Section: Estimation Of Total Emissions and Net Climate Effect Of Cookmentioning
confidence: 88%
“…Moreover, recent studies showed that many improved biomass cookstoves on the market today, though a great improvement regarding traditional cooking, still produce enough PM 2.5 and BC emissions to be considered a health and environmental hazard (Grieshop et al, 2011;Jetter et al, 2012;Kar et al, 2012;Mazorra, 2017;Smith et al, 2014;Sota et al, 2014).…”
Section: Overview Of Clean and Improved Cooking Solutions And Relatedmentioning
confidence: 99%
See 2 more Smart Citations